2009
DOI: 10.1371/journal.pone.0006966
|View full text |Cite|
|
Sign up to set email alerts
|

Alpha-Glucosidase Promotes Hemozoin Formation in a Blood-Sucking Bug: An Evolutionary History

Abstract: BackgroundHematophagous insects digest large amounts of host hemoglobin and release heme inside their guts. In Rhodnius prolixus, hemoglobin-derived heme is detoxified by biomineralization, forming hemozoin (Hz). Recently, the involvement of the R. prolixus perimicrovillar membranes in Hz formation was demonstrated.Methodology/Principal FindingsHz formation activity of an α-glucosidase was investigated. Hz formation was inhibited by specific α-glucosidase inhibitors. Moreover, Hz formation was sensitive to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 49 publications
1
61
1
2
Order By: Relevance
“…1C suggest that three distinct mechanisms are involved in crystal growth, in such a way that in each phase the rates of crystal growth are distinct. Conceivably, in early periods (0e6 h), nucleation of the first heme crystals could be supported by the recently described a-glucosidase activity (Mury et al, 2009), which may be consistent with spots of heme-peroxidase staining within the PMVM as shown by Silva et al (2007). Then, a second highly efficient process, acts between 6 h and 24 h. Possibly, during this period, extension of small Hz crystals could be promoted by the hydrophilicehydrophobic interfaces provided by lipids from PMVM.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…1C suggest that three distinct mechanisms are involved in crystal growth, in such a way that in each phase the rates of crystal growth are distinct. Conceivably, in early periods (0e6 h), nucleation of the first heme crystals could be supported by the recently described a-glucosidase activity (Mury et al, 2009), which may be consistent with spots of heme-peroxidase staining within the PMVM as shown by Silva et al (2007). Then, a second highly efficient process, acts between 6 h and 24 h. Possibly, during this period, extension of small Hz crystals could be promoted by the hydrophilicehydrophobic interfaces provided by lipids from PMVM.…”
Section: Discussionsupporting
confidence: 64%
“…Silva et al, 2007 have shown that development of PMVM changes during blood digestion, in which maximum PMVM levels are detected seven days after a blood meal . They also demonstrate that PMVM levels are correlated with a-glucosidase activity and it seems that part of the heme crystallization activity is due to the nucleation action of a-glucosidase on Hz formation (Mury et al, 2009). Regarding the role of insect aging, since R. prolixus is an obligatory hematophagous insect, it is not surprising that all the insect's stages are capable of producing this heme crystal.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The process is promoted by PMVM, with the lipids playing a major role (Stiebler et al, 2010a). A protein, -glucosidase may also play a role in haemozoin formation in this organism (Mury et al, 2009). …”
mentioning
confidence: 99%